Alcohol intake and the risk of intracerebral hemorrhage in the elderly: The MUCH-Italy. (17th July 2018) - Costa, Paolo; Grassi, Mario; Iacoviello, Licia; Zedde, Marialuisa; Marcheselli, Simona; Silvestrelli, Giorgio; DeLodovici, Maria Luisa; Sessa, Maria; Zini, Andrea; Paciaroni, Maurizio; Azzini, Cristiano; Gamba, Massimo; et al.
Abstract : Objective: To investigate the role of alcohol as a causal factor for intracerebral hemorrhage (ICH) and whether its effects might vary according to the pathogenic mechanisms underlying cerebral bleeding. Methods: We performed a case-control analysis, comparing a cohort of consecutive white patients with ICH aged 55 years and older with a group of age- and sex-matched stroke-free controls, enrolled in the setting of the Multicenter Study on Cerebral Haemorrhage in Italy (MUCH-Italy) between 2002 and 2014. Participants were dichotomized into excessive drinkers (>45 g of alcohol) and light to moderate drinkers or nondrinkers. To isolate the unconfounded effect of alcohol on ICH, we used causal directed acyclic graphs and the back-door criterion to select a minimal sufficient adjustment set(s) of variables for multivariable analyses. Analyses were performed on the whole group as well as separately for lobar and deep ICH. Results: We analyzed 3, 173 patients (1, 471 lobar ICH and 1, 702 deep ICH) and 3, 155 controls. After adjusting for the preselected variables in the minimal sufficient adjustments, heavy alcohol intake was associated with deep ICH risk (odds ratio [OR], 1.68; 95% confidence interval [CI], 1.36–2.09) as well as with the overall risk of ICH (OR, 1.38; 95% CI, 1.17–1.63), whereas no effect was found for lobar ICH (OR, 1.01; 95% CI, 0.77–1.32). Conclusions: In white people aged 55 years and older, high alcohol intake might exert a causal effect on ICH, with a prominent role in the vascular pathologies underlying deep ICH.